Antibiotic Resistance Profile of E. coli Isolates from Lettuce, Poultry Manure, Irrigation Water, and Soil in Kumasi, Ghana - Abigail Abena Anokyewaa Appau; Linda Aurelia Ofori (International Journal of Microbiology)
Inputs such as irrigation water and poultry manure used in lettuce cultivation have been found to be associated with antibiotic-resistant pathogens. The study assessed the antibiotic resistance profile of Escherichia coli isolated from lettuce, poultry manure, irrigation water, and soil in Kumasi. One hundred and fifty-six samples of lettuce, irrigation water, soil, and manure were collected from three farms over a seven-week cultivation period (seedlings to harvest stage). E. coli were enumerated using standard methods. 98% of the samples were positive for E. coli. Geometric means for lettuce, irrigation water, and soil ranged from 2.0 × 105 to 1.67 × 107 MPN/100 ml while that of manure ranged from 2.0 × 105 to 1.31 × 107 MPN/100 ml. Generally, the microbial load of all parameters on all farms across the weeks was significant and exceeded World Health Organization (WHO) and International Commission on Microbiological Specifications for Foods (ICMSF) standard recommendations for food. Using the Kirby Bauer method, antibiotic sensitivity testing was performed against 225 biochemically confirmed E. coli with twelve antibiotics. Relatively high resistance was recorded for some members of the beta-lactam class: meropenem: 94.2%, ampicillin: 91.9%, cefuroxime: 95.1%, ceftriaxone: 94.7%, and cefotaxime: 94.2%. Eighty of the isolates were screened for extended spectrum beta lactamase (ESBL) production using cefotaxime (CTX) and cefotaxime/clavulanic acid (CTX/CLA) discs and three showed positive: one each from poultry manure, irrigation water, and soil. Polymerase chain reaction (PCR) confirmed the presence of blaCTX-M gene. The occurrence of antibiotic-resistant E. coli in vegetables and their production environment is alarming and poses serious health threats to the general public. The presence of blaCTX-M gene in E. coli from a vegetable production site recorded for the first time in Ghana requires enforcement by regulatory bodies on the inappropriate use of antibiotics in the country.